2023
DOI: 10.3390/biomedicines11041170
|View full text |Cite
|
Sign up to set email alerts
|

Microneurotrophin BNN27 Reduces Astrogliosis and Increases Density of Neurons and Implanted Neural Stem Cell-Derived Cells after Spinal Cord Injury

Abstract: Microneurotrophins, small-molecule mimetics of endogenous neurotrophins, have demonstrated significant therapeutic effects on various animal models of neurological diseases. Nevertheless, their effects on central nervous system injuries remain unknown. Herein, we evaluate the effects of microneurotrophin BNN27, an NGF analog, in the mouse dorsal column crush spinal cord injury (SCI) model. BNN27 was delivered systemically either by itself or combined with neural stem cell (NSC)-seeded collagen-based scaffold g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In addition, we have developed and patented synthetic C17derivatives of DHEA (named BNNs) (Calogeropoulou et al, 2009), shown to interact with NGF receptors, which are deprived of any harmful estrogenic or androgenic effects, in contrast to endogenous DHEA. BNN27, as the prototype member of these synthetic analogs for neurotrophins, has been extensively studied at the molecular level for its ability to selectively activate TrkA and p75NTR receptors, exerting strong neuroprotective effects mediated by the TrkA and p75NTR receptors in cell models of neurotoxicity and neurodegeneration (Pediaditakis et al, 2016b) as well as in in vivo models of diabetic retinopathy (Iban-Arias, 2018), demyelination (Bonetto, 2017), apomorhine-induced cognitive decline (Pitsikas et al, 2021) and spinal cord injury (Georgelou et al, 2023). In the present study, we sought to investigate whether BNN27 could mimic in vivo NGF actions against the AD phenotype and attenuate the well described AD-related neuropathology of the 5xFAD mice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have developed and patented synthetic C17derivatives of DHEA (named BNNs) (Calogeropoulou et al, 2009), shown to interact with NGF receptors, which are deprived of any harmful estrogenic or androgenic effects, in contrast to endogenous DHEA. BNN27, as the prototype member of these synthetic analogs for neurotrophins, has been extensively studied at the molecular level for its ability to selectively activate TrkA and p75NTR receptors, exerting strong neuroprotective effects mediated by the TrkA and p75NTR receptors in cell models of neurotoxicity and neurodegeneration (Pediaditakis et al, 2016b) as well as in in vivo models of diabetic retinopathy (Iban-Arias, 2018), demyelination (Bonetto, 2017), apomorhine-induced cognitive decline (Pitsikas et al, 2021) and spinal cord injury (Georgelou et al, 2023). In the present study, we sought to investigate whether BNN27 could mimic in vivo NGF actions against the AD phenotype and attenuate the well described AD-related neuropathology of the 5xFAD mice.…”
Section: Introductionmentioning
confidence: 99%
“…Georgelou et al investigated the effects of a combined treatment involving the administration of small-molecule mimetics of endogenous neurotrophins and neural stem cells, demonstrating the synergistic effect of this combination in a mouse model of SCI by means of functional and histological studies [23].…”
mentioning
confidence: 99%